Late Cretaceous ostracod fauna from the Shenjiatun section (Songliao Basin, Northeast China): Biostratigraphic and palaeoecological implications. (October 2017) - Wang, Yaqiong; Sames, Benjamin; Liao, Huanyu; Xi, Dangpeng; Pan, Yanhong
Abstract: This work provides the first detailed taxonomic study of ostracod species from the Shenjiatun section (Nenjiang Formation, Songliao Basin, northeast China). Ten species belonging to seven genera are recognized. At the species level, this ostracod fauna shows a high degree of endemicity. The ontogeny of two species is recognized in this study, and sexual dimorphism within Daqingella arca is unequivocally recognized for the first time. The ostracod fauna suggests that this fossil-bearing sedimentary succession should be assigned to members 3–4 (Campanian) of the Nenjiang Formation (mainly Member 3) instead of representing 'Quaternary sediments' as previously thought. On the basis of the ostracod fauna, Member 3 of the Nenjiang Formation at Shenjiatun represents a shallow-littoral, lacustrine depositional environment that, at least in the upper part of Member 3, potentially included less stable conditions characterized by smaller, ephemeral waterbodies and increased (non-marine, oligohaline) salinities through evaporation.